2017
DOI: 10.1002/glia.23143
|View full text |Cite
|
Sign up to set email alerts
|

An astroglial basis of major depressive disorder? An overview

Abstract: Depression is a chronic, recurring, and serious mood disorder that afflicts up to 20% of the global population. The monoamine hypothesis has dominated our understanding of the pharmacotherapy of depression for more than half a century; however, our understanding of the pathophysiology and pathogenesis of major depression has lagged far behind. Astrocytes are the most abundant and versatile cells in the brain, participating in most, if not all, of brain functions as both a passive housekeeper and an active play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 384 publications
(479 reference statements)
3
138
0
Order By: Relevance
“…Decrease in astrocyte count and GFAP expression are seen at many brain regions in MDD post-mortem studies [3235] and animal models of depression [8]. A recent reprot suggested that antidepressants could induce recovery of astrocytes in MDD, which could be a potential mechanism for their anti-depression effect [8]. To test whether n-3 PUFAs affect astrocyte formation, we observed the effect of n-3 PUFAs on astrocyte differentiation from iNSCs derived from SSRI-sensitive or -resistant MDD subjects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Decrease in astrocyte count and GFAP expression are seen at many brain regions in MDD post-mortem studies [3235] and animal models of depression [8]. A recent reprot suggested that antidepressants could induce recovery of astrocytes in MDD, which could be a potential mechanism for their anti-depression effect [8]. To test whether n-3 PUFAs affect astrocyte formation, we observed the effect of n-3 PUFAs on astrocyte differentiation from iNSCs derived from SSRI-sensitive or -resistant MDD subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Decrease in astrocyte count and GFAP expression are often seen in MDD post-mortem studies [32, 33] [34, 35] [50]. Astrocyte reduction was also observed in a variety of animal models of depression [8]. Antidepressants, including SSRIs, could increase/restore the astrocyte counts or GFAP staining, which positively correlated with attenuated “depression-indicators” in rodents [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Astrocytes play a major role in excitatory neurotransmission by controlling the glutamate–glutamine cycle, which is fundamental for the synaptic plasticity associated with cognitive processes (Araque & Perea, ; Oliveira, Krügel, Köles, Illes, & Wirkner, ; Perea & Araque, ; Perea, Sur, & Araque, ). Moreover, they have been proposed as an early contributor to the underlying pathogenesis of MDD (Haroon, Miller, & Sanacora, ; Liu, Teschemacher, & Kasparov, ; Sanacora & Banasr, ; Wang, Jie, Liu, Yang, & Gao, ). Reductions of astrocyte number and alterations of astroglial function in frontolimbic structures have been found in MDD patients and suicide victims (Banasr & Duman, ; Peng, Verkhratsky, Gu, & Li, ; Rajkowska & Stockmeier, ).…”
Section: Introductionmentioning
confidence: 99%